2018
DOI: 10.21474/ijar01/6571
|View full text |Cite
|
Sign up to set email alerts
|

Kim-1 and Ngal as Biomarkers of Nephropathy in Type Ii Diabetes.

Abstract: Background: clinically detectable diabetic nephropathy is based on albumin excretion and glomerular filtration rate that mainly reflects the glomerular damage. New biomarkers have arisen with the promise of detecting kidney damage prior to the currently used markers. Objectives: to assess the usefulness of the urinary neutrophil gelatinase-associated lipocalin and kidney injury molecule-1 for the early diagnosis of diabetic kidney disease in type2 diabetes mellitus and to estimate their relation to the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several studies have documented an estimation of KIM-1 in urine (uKIM-1) as a predictive indicator for AKI as it appears well before serum creatinine increases [ 68 ]. Fourth, Ali et al reported uKIM-1 with more specificity and sensitivity than urine albumin in diagnosing early stages of DKD [ 69 ], and Gohda et al reported a significant association of serum KIM-1 with a lower GFR rate. [ 70 ] Clinical studies have highlighted that uKIM-1 values were gradually increased in patients with T1DM and T2DM from normo- micro-macroalbuminuria [ 70 , 71 ].…”
Section: Tubular Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have documented an estimation of KIM-1 in urine (uKIM-1) as a predictive indicator for AKI as it appears well before serum creatinine increases [ 68 ]. Fourth, Ali et al reported uKIM-1 with more specificity and sensitivity than urine albumin in diagnosing early stages of DKD [ 69 ], and Gohda et al reported a significant association of serum KIM-1 with a lower GFR rate. [ 70 ] Clinical studies have highlighted that uKIM-1 values were gradually increased in patients with T1DM and T2DM from normo- micro-macroalbuminuria [ 70 , 71 ].…”
Section: Tubular Markersmentioning
confidence: 99%
“…Onset and progression (T1DM, T2DM) [74,78] Yes [75] Yes [72] KIM-1 Onset (T2DM) [69] Progression (T1DM) [90] n/a n/a L-FABP Progression (T2DM) [99] n/a Yes [79] Oxidative marker 8-OxodG Progression (T2DM) [104] Yes [84] Yes [86] Pentosidine Progression (T1DM, T2DM) [110,111] Yes [128] Yes [91] Inflammation MCP-1 Progression (T2DM) [113] Yes [115] n/a TNF-α Progression (T2DM) [98] Yes [100] Yes [101] TNF-α Receptors Progression (T1DM, T2DM) [104,129] Yes [107] n/a CTGF Predictor of ESRD (T1DM) [123] Yes [124] n/a IL-6…”
Section: Microparticles/microvesicles (Mps)mentioning
confidence: 99%